2000
DOI: 10.1034/j.1600-0404.2000.101004279.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum and cerebrospinal fluid cystatin C levels in vascular and Alzheimer's dementia

Abstract: These results indicate that lower than normal CSF cystatin C level is not a diagnostic marker in ischemic VD and CAA related to AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…We found that plasma and CSF levels of cystatin C did not discriminate between AD patients and age and gender-matched control patients, in agreement with previous findings [30]. Also, CSF measurements of cystatin C by sandwich ELISA in large collectives of sCJD, vCJD, and control samples was not discriminatory between these three groups.…”
Section: Discussionsupporting
confidence: 90%
“…We found that plasma and CSF levels of cystatin C did not discriminate between AD patients and age and gender-matched control patients, in agreement with previous findings [30]. Also, CSF measurements of cystatin C by sandwich ELISA in large collectives of sCJD, vCJD, and control samples was not discriminatory between these three groups.…”
Section: Discussionsupporting
confidence: 90%
“…DISCUSSION In this study, lower serum levels of cystatin C were associated with higher incidence of AD. Previous studies of the association between serum cystatin C and AD have reported conflicting results, one reporting no difference in cystatin C levels between AD cases and controls, 24 one reporting high cystatin C levels in AD, 25 and a third reporting low levels of cystatin C in AD. 12 These studies may all be limited by a crosssectional case-control design and limited adjustments for potential confounders.…”
Section: Resultsmentioning
confidence: 77%
“…12 These studies may all be limited by a crosssectional case-control design and limited adjustments for potential confounders. Also, the two first studies had smaller study samples (n ϭ 41 and n ϭ 66) 24,25 compared with the third (n ϭ 646). and that staining with cystatin C is increased in AD brains, whereas it is absent or minimal in brains from individuals who remained cognitively intact during life.…”
Section: Resultsmentioning
confidence: 99%
“…The levels of at least 7 of the novel biomarkers have been evaluated in AD subjects in other studies: no change was observed in plasma PAI-1 levels [44]; in agreement with our findings, two studies have reported increased CSF MIF in AD and MCI subjects [45], [46]; also consistent with our findings, increased fibrinogen levels have been observed in AD and MCI CSF [47] and in AD plasma [48], and increased plasma levels have been associated with an increased risk of future dementia [49]; results have been mixed regarding CSF FAS levels in AD [50], [51]; AD plasma/serum VEGF levels have been reported to be unchanged [52], [53], decreased [54], and increased [55], while CSF levels have been reported to be unchanged [56] or increased [57]; no change in CSF or serum levels of TNF RII in AD has been reported [58]; cystatin C findings have been inconsistent, with reports of serum/plasma levels unchanged [59], increased in AD [60] or in those who later develop AD [61], and decreased [62] or decreased levels associated with increased risk of future AD [63], while CSF levels have been reported to be unchanged [59], [64], decreased [65], or increased [21]. These inconsistent results may be due in part to the existence of a truncated form of cystatin C, which was found to be increased in AD CSF, while the full length protein was decreased [20], [21].…”
Section: Discussionmentioning
confidence: 99%